Exploring barriers of m-commerce adoption in SMEs in the UK: Developing a framework using ISM. (February 2019) - Rana, Nripendra P.; Barnard, Daniel J.; Baabdullah, Abdullah M.A.; Rees, Daniel; Roderick, Sian
Highlights: The concept of m-commerce has grown exponentially within business in the last decade. The paper aims to understand barriers of m-commerce adoption in SMEs in Wales. The paper used Interpretive Structural Modelling and MICMAC to develop a framework. A large number of the barriers of m-commerce adoption have high levels of driving power. The findings indicated perceived risk as the key driving barrier of m-commerce adoption. The lack of customer trust and confidence depends the most on all other variables. Abstract: In the modern business era, mobile commerce (m-commerce) is changing the way the business is conducted using the Internet. However, the prominence of m-commerce among small and medium-sized enterprises (SMEs) in the UK is minimal. The purpose of this study is to evaluate the existing literature and to extend the research surrounding the barriers that prevent the adoption of m-commerce amongst SMEs. The study uses an Interpretive Structural Modelling (ISM) and MICMAC approach for guiding and helping managers of SMEs. Data was collected from an expert participant group each of whom had extensive knowledge of m-commerce. The findings represent the unstable nature of variables in the context of their impact on each other, their relationships, and themselves. The listed factors in the proposed framework and the interrelationships between them highlight the multi-dimensional element of m-commerce adoption prevention. This observation proves criticality of analysing data as a collective entity rather than viewing the barriers in isolation. The findings also indicated 'perceived risk' being a key barrier that demonstrates how personal opinions of the concept of adoption can have a great significance on the outcome and whether other variables will come into effect.